Comparative Analysis of the Effectiveness of Constitutional Remedies and Mentholum in the Management of Chronic Sinusitis – A Retrospective Case Analysis (Advancements in Homeopathic Research, 2024)
Chronic sinusitis is a prevalent condition that  significantly impacts quality of life. Conventional  treatments often provide limited relief, prompting  patients to seek alternative therapies. Homeopathy,  with its holistic approach, offers a promising option  for managing chronic sinusitis. This study aims to  evaluate the efficacy of constitutional homeopathic  remedies and Mentholum in addressing this condition. Methods A retrospective study was conducted to analyze case  reports of patients diagnosed with chronic sinusitis at  Sivaraj Homoeopathic Medical College & Research  Institute. Patients were categorized into two groups:  Group I (constitutional treatment) and Group II  (Mentholum 6CH treatment). The clinical course and  outcomes of both groups were assessed over a six month period. Results Both groups showed significant improvement in  symptoms. In Group I, 46% of patients experienced  mild improvement, and 41% experienced marked  improvement. In Group II, 34% of patients  experienced mild improvement, and 53% experienced  marked improvement. No statistically significant  difference was observed between the two groups in  terms of overall improvement. Conclusion This study suggests that both constitutional  homeopathic remedies and Mentholum can be  effective in managing chronic sinusitis. Further  research with larger sample sizes and randomized  controlled trials is warranted to validate these  findings and establish the long-term efficacy of these  approaches.
Keywords: Sinusitis; Mentholum; Homoeopathy; Constitutional Medicines